2020
DOI: 10.1108/ijpsm-06-2020-0150
|View full text |Cite
|
Sign up to set email alerts
|

Let me go to the office! An investigation into the side effects of working from home on work-life balance

Abstract: PurposeThe disruptions brought by COVID-19 pandemic compelled a large part of public sector employees to remotely work from home. Home-based teleworking ensured the continuity of the provision of public services, reducing disruptions brought by the pandemic. However, little is known about the implications of telecommuting from home on the ability of remote employees to manage the work-life interplay. The article adopts a retrospective approach, investigating data provided by the sixth European Working Conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
253
3
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(286 citation statements)
references
References 63 publications
12
253
3
18
Order By: Relevance
“…This background has also been observed in other regions of the world [ 22 ], as well as among Chilean teachers, who reported a significant association between low QoL perception and the mental component summary dimension among younger teachers (≤44 years vs. ≥45 years) [ 15 ]. Additionally, during the pandemic, the scores dropped significantly; this may be due to the impact of teleworking on teachers’ health, as reported in other groups of workers, who indicated that it was a principal factor impacting psychosocial health and physical burnout due to stress and work exhaustion among employees [ 2 , 3 , 4 ]. However, more studies are required to evaluate the effect of telework on teachers during the COVID-19 pandemic, as these results could also be due to other factors not explored in the present study, such as a decrease in social relations, domestic confinement, and a reduction in physical activity levels [ 31 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This background has also been observed in other regions of the world [ 22 ], as well as among Chilean teachers, who reported a significant association between low QoL perception and the mental component summary dimension among younger teachers (≤44 years vs. ≥45 years) [ 15 ]. Additionally, during the pandemic, the scores dropped significantly; this may be due to the impact of teleworking on teachers’ health, as reported in other groups of workers, who indicated that it was a principal factor impacting psychosocial health and physical burnout due to stress and work exhaustion among employees [ 2 , 3 , 4 ]. However, more studies are required to evaluate the effect of telework on teachers during the COVID-19 pandemic, as these results could also be due to other factors not explored in the present study, such as a decrease in social relations, domestic confinement, and a reduction in physical activity levels [ 31 ].…”
Section: Discussionmentioning
confidence: 91%
“…In this context, teleworking is a factor that has been a major challenge for some professionals, with a lack of control over working hours and increased psychosocial risks associated with stress and work overload [ 2 , 3 ]. Furthermore, teleworking has had a significant impact on professional and personal life (work–life balance), producing physical and mental exhaustion and burnout [ 4 ]. Additionally, the increase in digital technologies at work has increased stress in workers (techno-stress), which is associated with significant psychosocial demands [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Voluntary WFH is often adopted by employees as a strategy to adapt work to private life, motivated by family and household needs [ 14 ], and may be practiced mainly by employees having favorable conditions for WFH in terms of family life, household chores and workstation at home. Less voluntary WFH during the pandemic, likely performed even under unfavorable conditions, may be associated with changed physical behaviors because of these contextual differences [ 15 , 16 ]. More research on the trade-off between positive and negative aspects of WFH is therefore needed as a basis for policy recommendations during and beyond the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Synchronicity in time and space is becoming less important, and this may increase adaptability and flexibility (e.g., in terms of arrangements for meetings and working hours). However, it may also result in greater work-related fatigue, worsening the perceived work-life balance (Palumbo, 2020). This trend was observed with the digital economy before COVID-19; in this vein, Degryse (2016) recognized that the intensification of 'anytime, anywhere' work might blur the boundary between private life and working life, leading to stress and burnout.…”
Section: Finance and Infrastructurementioning
confidence: 99%